Natural selection against a circadian clock gene mutation in mice - Kamiel Spoelstra; Martin Wikelski; Serge Daan; Andrew Loudon; Michaela Hau (2015)
Significance The circadian clock has evolved to anticipate daily events and is assumed to be important for Darwinian fitness. The endogenous period of the clock runs close to 24 h, permitting accurate entrainment to the natural light/dark cycle. Circadian clocks with abnormal periods are therefore predicted to have negative consequences for fitness. We compared the fitness of mice with deviant circadian periods in populations living in a seminatural environment. Mice with near 24-h “resonant” rhythms survived longer and reproduced more than mice with rhythms shortened by a mutation in the circadian Ck1ε allele. Apart from the fundamental importance of such fitness effects in nature, this finding may have implications for humans subjected to circadian-rhythm deviations under abnormal work and lighting schedules.